The Problem of the Interaction Between Metaphysics and Natural Science in the Philosophy of Science - Plėšnys, Albinas (Problemos, 1996)
The understanding of the interaction between metaphysics and natural science in the modern philosophy of science is determined by empiricist tradition. The expression of the most negative point of view is presented by the empiricist criterion of meaning, proposed by logical empiricists. The criterion of demarcation between science and metaphysics, suggested by K. R. Popper, rehabilitates metaphysics in part, but it is purely factual. This is why it is not acceptable. For the more successful investigation of the interaction between metaphysics and science, the definition of metaphysics and the determination of its content is necessary. The Thomist solution to this problem in the theory of Double Truth is a paradigmatic example for the investigation of the interaction between science and metaphysics. Besides this, such investigation must be equally historical as logical.